Assonanze planistiche ed obiettivi produttivistici dell’Alta Autorità Ceca - Isoni, Alessandro (Rivista di studi politici internazionali, 2010)
The paper analyzes the influence of third way ideologies on the Ecsc High Authority, particularly with regard to its duties and organisation. Starting from the scientific debate about the legal status of the first successful attempt of European integration, the Author reconstructs a set of ideal and personal links between groups and people operating throughout the Thirties and Forties of the XXth century in France and some economic measures adopted in the same country during the postwar period. In this line, it is easier to understand some administrative and economic novelties introduced by the Monnet Plan for the French industrial reconstruction and the Schuman Plan, both elaborated by Jean Monnet and his staff. In this line, the Author underlines how Jean Monnet was deeply inspired by Paul Reuter, Pierre Uri and, last but not least, Jean Fourastié, who played a very important advisory role, pushing Monnet to invent a model that was able to blend European planism and American productivism in an original supranational public power. Cet essai analyse l'influence des idéologies de la troisième voie sur la définition des fonctions administratives et de l'organisation de la Haute Autorité de la Communauté européenne du charbon et de l'acier. À partir du débat scientifique sur la nature juridique du premier tentative réussi d'integration européenne, l'Auteur reconstruit toute une gamme de liens personnels et idéaux entre groupes et personnes qui opérèrent en France pendant les années Trente et Quarante du XXème siècle et certaines choix politiques adoptées pendant l'immédiat après-guerre par les gouvernements de la Quatrième République. Ce cadre interprétatif permet de comprendre plus aisément certaines nouveautés administratives et économiques introduites par le Plan de modernisation et d'équipement et le Plan Schuman, tous les deux élaborés par l'équipe qui entourait Jean Monnet. À ce propos, l'Auteur souligne que Jean Monnet fut inspiré par Paul Reuter, Pierre Uri et, surtout, par Jean Fourastié, qui jouèrent un rôle très important dans l'élaboration du projet de Communauté européenne du charbon et de l'acier, en poussant Jean Monnet à inventer un modèle institutionnel supranational capable de mélanger avec succès le planisme européenne au productivisme américain. PAROLE CHIAVE: Comunità europea del carbone e dell'acciaio; Alta Autorità; Jean Monnet; Produttivismo; Terza via.